2015
DOI: 10.1161/strokeaha.114.007385
|View full text |Cite
|
Sign up to set email alerts
|

Left-Sided Strokes Are More Often Recognized Than Right-Sided Strokes

Abstract: This study was embedded within the prospective population-based Rotterdam Study 8 and Rotterdam Scan Study. 9 From 1990 to 2012, we continuously followed up 13 894 participants (mean age, 65.5±10.3 Background and Purpose-Left-sided strokes are reported to be more common than right-sided strokes, but it is unknown whether they occur more often or are simply recognized more easily by clinicians. In a large unselected communitydwelling population, we examined the frequency of clinical left-and right-sided stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 11 publications
4
35
2
1
Order By: Relevance
“…We also showed a higher prevalence of left-sided ischemic lesions compared to right-sided lesions and that this difference in prevalence also could be observed for the largest subgroups of patients with supratentorial lesions and lesions in the MCA territory. Left-sided lesions were also more common on CT in a recent population-based cohort (8,9). In our material, this difference is caused mainly by a difference in supratentorial lesions in the MCA territory.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…We also showed a higher prevalence of left-sided ischemic lesions compared to right-sided lesions and that this difference in prevalence also could be observed for the largest subgroups of patients with supratentorial lesions and lesions in the MCA territory. Left-sided lesions were also more common on CT in a recent population-based cohort (8,9). In our material, this difference is caused mainly by a difference in supratentorial lesions in the MCA territory.…”
Section: Discussionsupporting
confidence: 50%
“…Several population-based MRI initiatives, such as the Rotterdam and Framingham studies, have provided valuable insights into the prevalence of cerebral infarcts (6,7), including the distribution with regard to laterality (8,9). However, there are few large MRI-based stroke registries (10), and additional insights can be gained in understanding the AIS characteristics on MRI across a multiethnic, hospital-based cohort.…”
Section: Introductionmentioning
confidence: 99%
“…This theory was supported by evidence from the Rotterdam population based study demonstrating that there were more incident left than right hemisphere strokes reported but equal prevalence of left and right cerebral hemisphere infarcts on magnetic resonance imaging (Portegies et al, 2015).…”
Section: Cerebrovascular Disease Impacting the Visual Pathwaymentioning
confidence: 88%
“…This predilection may in theory be due to differences in shear stress resulting from anatomical differences between the left and right carotid arteries and plaque components. While the increased diagnosis of stroke in the left hemisphere may be related to the underdiagnoses of right hemisphere stroke in clinical practice, 35, 36 the possibility of differences in plaque components and hemodynamic differences remains to be rigorously studied. Recently, differences in plaque components have been described and our findings of sidedness are in line with these.…”
Section: Discussionmentioning
confidence: 99%